СРАВНИТЕЛЬНЫЙ АНАЛИЗ МЕЖДУНАРОДНЫХ СТАНДАРТОВ МАТЕМАТИЧЕСКОГО ОБРАЗОВАНИЯ (PISA, TIMSS) В УЗБЕКИСТАНЕ - Изетаева, Г.К. (SCIENCE and SOCIETY, 2025)
The article is dedicated to a comparative analysis of international PISA and TIMSS studies in the context of reforming mathematics education in Uzbekistan. Recommendations for adapting teaching methods and learning content aimed at increasing the competitiveness of schoolchildren in the international arena have been proposed. The research has theoretical and practical significance for the further development of Uzbekistan educational policy in the context of globalization.